Acompanhamento terapêutico na psicose: possibilidades de uma orientação analítica - Anamaria Batista Nogueira (2007)
The subject matter of this work is to investigate the clinical and theoretical aspects of Therapeutic Accompaniment (TA)2 through psychoanalytical aid using primarily the conceptual tools of transferral and imagination. The general objective is to observe howpsychoanalysis can contribute in the clinical process. It consists of a therapeutic assistant guided by the psychoanalytical theory. After a revised bibliographic history about TA combined with research made by professionals in the Mental Health field in Belo Horizonte and the UFMG (Universidade Federal de Minas Gerais Federal University of Minas Gerais), a portrayal of TA is proposed, from its origins to thepresent time, emphasising the progress and setbacks within the Mental Health area. In regards to the psychoanalytical theory, if on one hand Freud considered the psychotic treatment unviable, on another hand a possibility of psychotic treatment is feasible through TA based on Lacans beliefs. In order to illustrate such argument many cases oftherapeutic assistants who work or have worked in programmes or institutions of great importance for the history of TA in Belo Horizonte will be used as a reference. These are some of the institutions: · PAI-PJ (Programme of Integral Assistance to the Judiciary Patient); · PDP (Programme of Psychiatric De-hospitalisation); · CERSAM (Centre of Health Mental Reference); · Clinica Urgentemente.